2020
DOI: 10.1088/1755-1315/599/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Rice husk-based biochar for carbon dioxide adsorption in biogas

Abstract: Rice husk-based biochar has been prepared by pyrolysis process for carbon dioxide adsorption in biogas. Biochar is considered as porous material for carbon dioxide adsorption. In this study, the adsorption of carbon dioxide, the largest impurity in biogas, was evaluated. The adsorptions were conducted in five treatments (mass variation): 80 grams of biochar (RB1), 60 grams of biochar and 20 grams of zeolite (RB2), 40 grams of biochar and 40 grams of zeolite (RB3), 20 grams of biochar and 60 grams of zeolite (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Sugiarto et al [5] reported that zeolite attracts to capture carbon dioxide because it has strong electro-positivity and attracts acidic character like carbon dioxide molecules [13]. Rice husk-based biochar is reported to have larger pore surface area than that of natural zeolite [10] so the ability to adsorb carbon dioxide increased but not significantly when 25% volume of natural zeolite was replaced by rice husk-based biochar. The substitution of natural zeolite with biochar with the proportion of 25% of total volume would maximize the pore area that has the function to capture carbon dioxide molecules.…”
Section: Biogas Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugiarto et al [5] reported that zeolite attracts to capture carbon dioxide because it has strong electro-positivity and attracts acidic character like carbon dioxide molecules [13]. Rice husk-based biochar is reported to have larger pore surface area than that of natural zeolite [10] so the ability to adsorb carbon dioxide increased but not significantly when 25% volume of natural zeolite was replaced by rice husk-based biochar. The substitution of natural zeolite with biochar with the proportion of 25% of total volume would maximize the pore area that has the function to capture carbon dioxide molecules.…”
Section: Biogas Purificationmentioning
confidence: 99%
“…This study investigates the use of rice husk-based biochar for biogas purification that is considered rare. The previous study had used rice husk-based biochar combined with natural zeolite for biogas purification in the mass ratio [10]. However, based on the study evaluation, the mass ratio between natural zeolite and biochar cannot be compared to each other because of the density.…”
Section: Introductionmentioning
confidence: 99%